"Positive Learning Attitude" Training to Improve Vocational High School Students' Understanding of Academic Cyberslacking - Simanjuntak, Ermida; Apsari, Yuni; Engry, Agustina (Psikostudia : Jurnal Psikologi, 2022)
Online learning at home for vocational high school students triggers several problems, including academic cyberslacking. Academic cyberslacking is defined as students' internet access to things unrelated to the course materials during the class. Referring to this condition, vocational high school students need to have a better understanding of academic cyberslacking through training so that the students can control the emergence of academic cyberslacking during the class. This study explores the effect of positive learning attitude training on increasing the understanding of vocational high school students in academic cyberslacking. The participants of this study were 187 vocational high school students who participated in a positive learning attitude training. The results showed a value of Z = -3,306, p = 0.001 (p<0.05), so it can be concluded that there is a significant difference in the understanding of academic cyberslacking before and after participating in positive learning attitude training of the vocational high school students. Students understand better the academic cyberslacking phenomenon after receiving positive learning attitude training.Situasi belajar daring di rumah pada siswa Sekolah Menengah Kejuruan memicu beberapa permasalahan salah satunya adalah cyberslacking akademik. Cyberslacking akademik didefinisikan sebagai akses internet pada hal-hal tidak berhubungan dengan materi pelajaran yang sedang diikuti oleh siswa. Merujuk pada kondisi ini maka siswa Sekolah Menengah Kejuruan perlu mendapatkan pemahaman mengenai cyberslacking akademik melalui suatu training sehingga siswa dapat mengendalikan kemunculan cyberslacking akademik saat mengikuti pelajaran. Penelitian ini bertujuan untuk melihat pengaruh training positive learning attitude pada peningkatan pemahaman siswa Sekolah Menengah Kejuruan pada cyberslacking akademik. Subjek penelitian adalah 187 siswa Sekolah Menengah Kejuruan yang mengikuti training positive learning attitude. Hasil penelitian menunjukkan nilai Z = -3.306, p = 0.001 (p<0.05) sehingga dapat disimpulkan bahwa ada perbedaan yang signifikan pada pemahaman siswa Sekolah Menengah Kejuruan pada cyberslacking akademik sebelum dan sesudah mengikuti training positive learning attitude. Pemahaman siswa pada fenomena cyberslacking akademik meningkat setelah mendapatkan training positive learning attitude.